SP4N-LAPOR AS AN ONLINE INFORMATION AND COMMUNICATION SERVICE FOR THE PEOPLE OF PONOROGO REGENCY - Ambarsari Hasnaa Nur Azizah Hasnaa; Barnad (Jurnal Bisnis Terapan, 2022)
SP4N-LAPOR is a facility provided to provide information and seek information from the public on the performance of the government. This facility is made based on the mandate of the Law of the Republic of Indonesia. The Ponorogo Regional Government since 2017 has provided this facility. Narrative research is used to determine the quality of service utilization of LAPOR and the follow-up of the data that has been collected by this facility. The research method used are surveys, observation, and interviews. The survey was conducted on people who use SP4N-LAPOR facilities and come to the offices of Regional Apparatus Organizations. The number of survey data obtained is 162 units. The results of statistically processing the data according to the guidelines of the PANRB Ministerial Regulation of the Republic of Indonesia number 14 of 2017 obtained an average value of 81.56. This value indicates that the service quality is included in the good category. Observation and interview methods were conducted on employees who are responsible for processing complaint data made by the public through SP4N-LAPOR. The performance of the employee affects the time for problem-solving, while the community demands that problems that occur immediately be followed up. Obstacles like this will make a poor assessment of the performance of services that have been provided by the government. This fact is in accordance with the value of the questionnaire for handling complaints, suggestions, and inputs, which is 2.895 which is included in the poor category.